L'impact des facteurs sociodémographiques et la formation en entrepreneuriat sur l’émergence de l’idée d’entreprendre chez les étudiants marocains - Nabil RIZQI; Hajar EL HASSANI (African Scientific Journal, 2022)
Some statistical patterns have been identified in the course of studying the idea of entrepreneurship among young Moroccan students while focusing on the demographic characteristics that determine the likelihood of becoming an entrepreneur. The elements studied include gender, age, level, and type of education pursued. The results showed/ that men are more likely to start a business than women (in a ratio of about ¾) and that entrepreneurs are generally of a higher educational level compared to the average citizen. However, this stream of research is subject to an important limitation that is common to the personality trait approach since both schools of thought assume that different psychological and demographic characteristics have the same consequences regardless of the context in which the potential entrepreneur is situated. Yet, being set in an environment that favours the founding of a business and being stimulated by external reasons to start a business can also have an influence on the individual who, with the same characteristics, wouldn’t carry out the same actions. To address this topic, the adopted research methodology is of a hypothetico-deductive nature, as it is based on the verification of a range of hypotheses among 300 students with a predominantly entrepreneurial background.